1988
DOI: 10.1016/0014-5793(88)80387-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic signal sequences (PEST) in the mammalian aminoacyl‐tRNA synthetase complex

Abstract: Eight aminoacyl-tRNA synthetases together with three unidentified proteins are associated as a multi-enzyme complex in mammalian cells. Partial peptide sequences for lysyl-and aspartyl-tRNA synthetases are determined and no highly hydrophobic peptides are found. The partial amino acid sequences for two of the unidentified proteins in the complex are shown to have substantial homology and each has a number of unique sequences. The results suggest that the two unidentified proteins are fragments of synthetases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The fusion of a new domain to an existing protein is a straightforward way to introduce a new function. Indeed, compared with their prokaryotic or lower eukaryotic counterparts, all human AARS (except for AlaRS) have extra domains or motifs at either the N‐ or C‐terminus [5,21,22] (Fig. 1 ).…”
Section: Functional Expansion Through Acquisition Of Extra Domainsmentioning
confidence: 99%
“…The fusion of a new domain to an existing protein is a straightforward way to introduce a new function. Indeed, compared with their prokaryotic or lower eukaryotic counterparts, all human AARS (except for AlaRS) have extra domains or motifs at either the N‐ or C‐terminus [5,21,22] (Fig. 1 ).…”
Section: Functional Expansion Through Acquisition Of Extra Domainsmentioning
confidence: 99%
“…As previously observed by electrofocusing analysis of the complex (28), the p43 polypeptide displays a markedly basic pI, evaluated to 9.4 according to its amino acid sequence. The sequences of the three peptides obtained from the p43 component of the sheep complex (Table I) as well as some peptide sequences issued from the rat p43/p38 components (27) were recovered in the protein sequence derived from the cloned cDNA (Fig. 1).…”
Section: Identification Of the Deduced Protein As The P43 Component Omentioning
confidence: 99%
“…The hamster, human, and mouse proteins share only about 60 and 70% of identical residues, respectively for domains III and IV. Domain III has a high serine content (10 Ser, residues 120 -157), whereas domain IV (residues 158 -193) is distinctly hydrophilic, with a stretch of lysine and glutamate Table I determined for the sheep p43 protein are double-underlined; those that were determined for the rat p38/p43 proteins (27) are underlined. The upstream in-frame TGA stop codon, the putative polyadenylation signal, and the poly(A) tract are indicated by a dotted line.…”
Section: Identification Of the Deduced Protein As The P43 Component Omentioning
confidence: 99%
See 1 more Smart Citation
“…Aminoacyl-tRNA þ AMP Since bacterial and yeast synthetases occur as free soluble enzymes in cytoplasm under normal conditions, the organization of aaRS's in mammalian cells as a supramolecular assemblage may reveal the evolutionary pressure on the organization of protein biosynthetic machinery [11]. Assessment of the complex and free forms of synthetases indicated that the synthetases complex may provide stabilization against thermal or chemical activation [12] and probably against intracellular proteolysis [13] and to control the synthetase activity. This ubiquitous assembly consists of 11 polypeptide subunits of M r ranging from 18 to 160 kDa which can be purified to homogeneity [14].…”
Section: Introductionmentioning
confidence: 99%